Numerical Investigation on Interference of Multiple Hydraulic Fractures in Layered Formation - Li, Zhichao; Wang, Shuren; Li, Lianchong; Zhang, Jiyun (Frontiers in Earth Science, 2022)
Staged treatment in vertical wells is extensively applied in layered formation to obtain commercial exploitation of hydrocarbon resource. Huge size heterogeneities always exist between multiple hydraulic fractures in different layers. To reveal the interference of multiple hydraulic fractures in layered formation, a series of numerical investigations were conducted based on the cohesive zone finite element method. Results show the sole stress interference is too small to exert an effective impact on adjacent pay zones, which is quite different from those in horizontal wells. The fracture size heterogeneities are mainly caused by the interference of the fluid flow into multiple perforation tunnels in different pay zones. To further make clear how the flow distribution in the pay zones is affected, five related factors, including the perforating thickness, pay zone thickness, rock permeability, the minimum horizontal stress of pay zone and the rock strength, are respectively analyzed. Results show it is through the manner of flow distribution adjustment in each pay zone do the five factors affect the fracture size. This study is of critical importance to clarify how the multiple hydraulic fractures from vertical well interfere in layered formation, and explain why the hydraulic fractures we get in field is far away from what we want in ideal.